Math Calculators, Lessons and Formulas

It is time to solve your math problem

mathportal.org
« Common derivatives formulas - exercises
Differentiation: (lesson 2 of 3)

Product and Quotient Rule for Derivatives

Product Rule

Let f(x)f(x) and g(x)g(x) be differentiable at xx. Then h(x)=f(x)g(x)h(x) = f(x) g(x) is differentiable at xx and

(f(x)g(x))=f(x)g(x)+f(x)g(x)\color{blue}{(f(x) \cdot g(x))' = f'(x) \cdot g(x) + f(x) \cdot g'(x)}

We illustrate product rule with the following examples:

Example 1:

(x3ex)=(x3)(ex)+x3(ex)=3x2ex+x3ex==x2ex(3+x) \begin{aligned} (\color{blue}{x^3} \cdot \color{red}{e^x})' &= \color{blue}{(x^3)'} \cdot \color{red}{(e^x)'} + \color{blue}{x^3} \cdot \color{red}{(e^x)'} \\ &= 3 \cdot x^2 \cdot e^x + x^3 \cdot e^x = \\ &= x^2 e^x (3 + x) \end{aligned}

Example 2:

((x+2)(x2x+1))=(x+2)(x2x+1)+(x+2)(x2x+1)==1(x2x+1)+(x+2)(2x1)==x2x+1+x2x+4x2==2x2+2x1 \begin{aligned} (\color{blue}{(x + 2)} \cdot \color{red}{(x^2 - x + 1)})' &= \color{blue}{(x + 2)'} \cdot \color{red}{(x^2 - x + 1)} + \color{blue}{(x + 2)} \cdot \color{red}{(x^2 - x + 1)'} = \\ &= 1 \cdot (x^2 - x + 1) + (x + 2) \cdot (2x - 1) = \\ &= x^2 - x + 1 + x^2 - x + 4x - 2 = \\ &= 2x^2 + 2x - 1 \end{aligned}

Try yourself

[(x2+3x1)ex]= \color{blue}{[ ( x^2 + 3x - 1 ) \cdot e^x ]' = }
(x25x2)ex ( x^2 - 5x - 2 ) \cdot e^x (x25x+2)ex ( x^2 - 5x + 2 ) \cdot e^x (x2+5x2)ex ( x^2 + 5x - 2 ) \cdot e^x (x2+5x+2)ex ( x^2 + 5x + 2 ) \cdot e^x

Quotient rule:

Let f(x)f(x) and g(x)g(x) be differentiable at xx with g(x)0g(x) \ne 0. Then f(x)g(x)\frac{f(x)}{g(x)} is differentiable at xx and

[f(x)g(x)]=f(x)g(x)f(x)g(x)[g(x)]2\color{blue}{\left[\frac{f(x)}{g(x)}\right]' = \frac{f'(x) \cdot g(x) - f(x) \cdot g'(x)}{[g(x)]^2}}

We illustrate quotient rule with the following examples:

Example 3:Differentiate y=x22+xy = \frac{x^2}{2 + x}

Solution 3:

(x22+x)=(x2)(2+x)x2(2+x)(2+x)2==2x(2+x)x2(0+1)(2+x)2==4x+2x2x2(2+x)2==x2+4x(2+x)2 \begin{aligned} \left( \frac{\color{blue}{x^2}}{\color{red}{2 + x}} \right)' &= \frac{\color{blue}{(x^2)'} \cdot \color{red}{(2 + x)} - \color{blue}{x^2} \cdot \color{red}{(2 + x)'}}{\color{red}{(2 + x)^2}} = \\ &= \frac{2x \cdot (2 + x) - x^2 \cdot (0+1)}{(2 + x)^2} = \\ &= \frac{4x + 2x^2 - x^2}{(2 + x)^2} = \\ &= \frac{x^2 + 4x}{(2 + x)^2} \end{aligned}

Try yourself

(3+xx2)= \color{blue}{\left( \frac{3 + x}{x^2} \right)' = }
x+6x3 \frac{x + 6}{x^3} x+6x3 - \frac{x + 6}{x^3} x+6x4 \frac{x + 6}{x^4} x+6x4 -\frac{x + 6}{x^4}

Example 4:Differentiate y=lnx1+x2y = \frac{\ln x}{1 + x^2}

Solution 4:

(lnxx2)=(lnx)x2lnx(x2)(x2)2==1xx2lnx2xx4==x2xlnxx4==x(12lnx)x4==12lnxx3 \begin{aligned} \left( \frac{\color{blue}{\ln x}}{\color{red}{x^2}} \right)' &= \frac{\color{blue}{(\ln x)'} \cdot \color{red}{x^2} - \color{blue}{\ln x} \cdot \color{red}{(x^2)}}{\color{red}{(x^2)^2}} = \\ &= \frac{\frac{1}{x} \cdot x^2 - \ln x \cdot 2x}{x^4} = \\ &= \frac{x - 2 x \ln x}{x^4} = \\ &= \frac{x (1 - 2 \ln x)}{x^4} = \\ &= \frac{1 - 2 \ln x}{x^3} \end{aligned}

Try yourself

(lnxx2+x)= \color{blue}{\left( \frac{\ln x}{x^2 + x} \right)' = }
x+1(2x1)lnx(x2+x)2 \frac{x + 1 - ( 2x - 1 ) \ln x}{{(x^2 + x)}^2} x1+(2x1)lnx(x2+x)2 \frac{x - 1 + ( 2x - 1 ) \ln x}{{(x^2 + x)}^2} x+1(2x+1)lnx(x2+x)2 \frac{x + 1 - ( 2x + 1 ) \ln x}{{(x^2 + x)}^2} x1+(2x+1)lnx(x2+x)2 \frac{x - 1 + ( 2x + 1 ) \ln x}{{(x^2 + x)}^2}

Example 5:Differentiate y=tanxy = \tan x

Solution 5:

(sinxcosx)=(sinx)cosxsinx(cosx)(cosx)2==cosxcosxsinx(sinx)cos2x==cos2x+sin2xcos2x==1cos2x \begin{aligned} \left( \frac{\color{blue}{\sin x}}{\color{red}{\cos x}} \right)' &= \frac{\color{blue}{( \sin x )'} \cdot \color{red}{\cos x} - \color{blue}{\sin x} \cdot \color{red}{(\cos x)'}}{\color{red}{(\cos x)^2}} = \\ &= \frac{\cos x \cdot \cos x - \sin x \cdot ( - \sin x)}{{\cos}^2 x} = \\ &= \frac{{\cos}^2 x + {\sin}^2 x}{{\cos}^2 x} = \\ &= \frac{1}{{\cos}^2 x} \end{aligned}

Try yourself

(cotx)= \color{blue}{( \cot x )' = }
1cos2x \frac{1}{\cos^2 x} 1cos2x - \frac{1}{\cos^2 x} 1sin2x \frac{1}{\sin^2 x} 1sin2x - \frac{1}{\sin^2 x}